(untitled) (Dialogos, 2017)
O texto aborda aspectos do campo dos estudos da criminologia referidos Ã cultura religiosa e suas implicações na cultura jurídica. O processo de passagem Ã modernidade na Europa e seus desdobramentos para o mundo lusobrasileiro (fins do século XVIII e primeira metade do XIX) são analisados a partir das concepções sobre crime/punição presentes no pensamento jurídico, tendo em vista as relações entre direito e religião. Abstract. The essay focuses on aspects of criminology studies, concerning religious culture and its relations with juridical culture. The process of transition to modernity in Europe, and its expansion to the Portuguese-Brazilian world (from the late 18th century to the first half of the 19th century) are analyzed; the conceptions of crime/punishment in juridical thought are taken in account, through the relations between Law and Religion.